How to explain a PaO2 of 140 mmHg in a venous line? - Mizzi, A.; Landoni, G.; Corno, L.; Fichera, et al., M. (Acta Biomedica Atenei Parmensis, 2009)
Metformin is a commonly used oral antidiabetic drug which can cause lactic acidosis. Although rare, this condition carries a high mortality risk. Correction of metabolic acidaemia is essential for treatment and dialysis with bicarbonate replacement is the gold standard approach. A 53-year-old man with diabetes on metformin therapy was admitted to the intensive care unit with severe lactic acidosis and acute renal failure suggesting metformin intoxication. The lactic acidosis was treated with bicarbonate haemodialysis and his pH normalized after 10 hours, but he died because of myocardial infarction due to severe hypotension. At ICU admission an aortic dissection was also hypothesized but TEE did not evidence aortic dissection. The dilemma in this patient was represented by the abnormal PaO2 value (140 mmHg) in the venous blood gas analysis. Considering that metformin acts on mitochondrial respiration, the dilemma may be explained by hypothesizing a cellular respiration block caused by metformin or severe acidosis.